Consumer attitudes to fuel cell vehicles post trial in the United Kingdom. (27th April 2016) - Hardman, Scott; Chandan, Amrit; Shiu, Eric; Steinberger-Wilckens, Robert
Abstract: Fuel cell cehicles (FCVs) have clear societal and environmental benefits and can help mitigate the issues of climate change, urban air pollution and oil dependence. In order for FCVs to have the biggest impact on these issues they need to be employed in large numbers. First, though, they need to be adopted by consumers. Their acceptance depends on positive consumer attitudes towards the vehicles. Currently there is a limited understanding within the literature on how consumers perceive FCVs and what the likelihood of adoption by consumers would be, despite significant governmental and organisational investments into the technology. Therefore this study assesses consumer attitudes towards FCVs in the United Kingdom. 81 persons drove a Hyundai FCV at the Low Carbon Vehicle Event in September 2015 of which 30 took part in this study. The results show that at present FCVs are perceived mostly as being similar to incumbent internal combustion engine vehicles. This is an admirable technical achievement, however in order for consumers to adopt FCVs they will need to be perceived as having distinctive benefits. Two significant barriers to the adoption of FCVs are observed in this sample: high costs and lack of refuelling infrastructure. This paper goes on to make suggestions on how and which beneficial attributes of the vehicles can be promoted to consumers and also makes suggestions on how the barriers can be overcame so that FCVs will be adopted by consumers. Highlights: Early adopters perceptions of fuel cell vehicles (FCVs) in a trial environment are assessed. According to consumers FCVs are perceived mostly as similar to ICEVs and BEVs. FCVs have better range and time to refuel compared to a BEV. FCVs have improved environmental impacts and performance compared to an ICEV. They however require more decisive benefits in order to convince consumer to adopt the vehicles given their current high costs.